The Sentiment Analysis on Social Media in the Viral Case of Gus Miftah and the Ice Seller that Encourages Digital Activism - Paskalia, Paskalia (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2025)
Social media has become a digital public space that fosters massive and spontaneous digital activism. This study aims to analyze public sentiment in the case of the viral video of Gus Miftah joking with an iced tea seller while preaching. The incident prompted widespread public discussion on social media, affecting Gus Miftah's reputation as a state figure and state official, leading to his resignation from the position of Special Presidential Envoy for Religious Harmony. This research method applies a quantitative approach with sentiment analysis based on big data of digital footprints on social media with Brand24 software. Researchers used the keywords "Gus Miftah" and "ice seller" in collecting data during December 1-15, 2024. The results showed a total of 6,519 mentions on social media with the highest number of mentions on Youtube, followed by X (Twitter), TikTok, and Facebook. The majority of sentiment was negative (80%), while positive sentiment was only 20%. This study shows a relationship between viral content, public opinion, and its impact on political decisions.